Practice Rehearsal Pairs: Inovasi Strategi Pembelajaran dalam Meningkatkan Kemampuan Menulis Al-Qur’an - Setiaji, Heri; Rofiq, Ahmad; Nasrudin, Anas; Lestari, Lesti (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2025)
Eligious Education is also intended as an effort to enhance the spiritual potential that shapes students with faith and belief in God Almighty, as well as obedience in fulfilling His commands and avoiding His prohibitions, while cultivating noble character. BTQ (Qur'an Reading and Writing) is a part of the Islamic Religious Education subject that serves as a means of providing knowledge, guidance, and development to students, particularly in Madrasah Ibtidaiyah, to understand and believe in the truth of Islamic teachings based on the Qur'an and As-Sunnah, and to practice its content in daily life. This study aims to examine the effect of using the Practice Rehearsal Pairs strategy in improving students' ability to write the Qur'an. This strategy is designed to encourage collaboration between students in practicing Qur'an writing techniques repetitively while providing feedback to each other. It is expected that through this approach, students will improve the accuracy, readability, and conformity of their writing to the rules of Qur'an writing. This research employs an experimental method with a pretest-posttest design involving two groups: an experimental group applying the Practice Rehearsal Pairs strategy and a control group using conventional learning methods. The results show that the application of the Practice Rehearsal Pairs strategy leads to significant improvements in students' Qur'an writing abilities, both in accuracy and readability, compared to the conventional method. These findings contribute to the innovation in Qur'an writing instruction and introduce a collaborative approach to learning.